The middle ages, sketches and fragments - Shahan, Thomas J. (Benziger brothers, 1904)
Gregory the Great and the barbarian world.--Justinian the Great (A. D.527-565)--The religion of Islam--Catholicism in the middle ages.--The Christians of Saint Thomas.--The medival teacher.--The book of a mediæval mother.--German schools in sixteenth century.--Baths and bathing in the middle ages.--Clergy and people in mediæval England.--The cathedral-builders of mediæval Europe.--The results of the crusades.--On the Italian renaissance.